Increased affective ultrasonic communication during fear learning in adult male rats exposed to maternal immune activation - Yee, Nicole; Schwarting, Rainer K.W.; Fuchs, Eberhard; Wöhr, Markus (Journal of psychiatric research, 2012)
Maternal exposure to infection during pregnancy greatly increases the risk of psychopathology in the offspring. In support of clinical findings, rodent models of maternal immune activation (MIA) show that prenatal exposure to pathogens can induce phenotypic changes in the offspring associated with schizophrenia, autism, depression and anxiety. In the current study, we investigated the effects of MIA via polyinosinic:polycytidylic acid (poly I:C) on emotional behavior and communication in rats. Pregnant rats were administered poly I:C or saline on gestation day 15 and male offspring were tested in an auditory fear conditioning paradigm in early adulthood. We found that prenatal poly I:C exposure significantly altered affective signaling, namely, the production of aversive 22-kHz ultrasonic vocalizations (USVs), in terms of call number, structure and temporal patterning. MIA led to an increase in aversive 22-kHz USVs to 300% of saline controls. Offspring exposed to MIA not only emitted more 22-kHz USVs, but also emitted calls that were shorter in duration and occurred in bouts containing more calls. The production of appetitive 50-kHz USVs and audible calls was not affected. Intriguingly, alterations in aversive 22-kHz USV emission were observed despite no obvious changes in overt defensive behavior, which highlights the importance of assessing USVs as an additional measure of fear. Aversive 22-kHz USVs are a prominent part of the rat’s defensive behavioral repertoire and serve important communicative functions, most notably as alarm calls. The observed changes in aversive 22-kHz USVs show that MIA has long-term effects on emotional behavior and communication in exposed rat offspring.